Facile Synthesis of Flower-like (BiO)2CO3@MnO2 and Bi2O3@MnO2 Nanocomposites for Supercapacitors. (20th June 2015) - Ma, Junjun; Zhu, Shijin; Shan, Qianyuan; Liu, Shifeng; Zhang, Yuxin; Dong, Fan; Liu, Hongdong
Graphical abstract: Highlights: (BiO)2 CO3 @MnO2 Core-shell Architecture: Controllable Hybrid Electrodes. Cycling stability: 125% retention after 1000 cycles. Higher specific capacitance: 196 F g −1 . Fabrication strategy: Facile Self-assembly. Abstract: Manganese dioxide (MnO2 )-decorated flower-like bismuth subcarbonate ((BiO)2 CO3 ) and calcined product (Bi2 O3 ) have been uniformly fabricated via a hydrothermal approach, and further investigated as the electrodes for supercapacitor. Both of the core-shell nanostructures displayed moderate capacities (196 F g −1 or 54.5 mAh g −1 for (BiO)2 CO3 @MnO2 and 139.4 F g −1 or 38.7 mAh g −1 for Bi2 O3 @MnO2 ) with superb cycling stability (125% for (BiO)2 CO3 @MnO2 and 112% for Bi2 O3 @MnO2 after 1000 cycles). The electrochemical properties of the electrode are strongly related to their high surface area, porous structure and good conductivity, which cannot only provide rich active sites but also shorten the ion transport pathways.